A Highly Stable Photodetector Based on a Lead-Free Double Perovskite Operating at Different Temperatures; Journal of Physical Chemistry Letters; Vol. 12, iss. 24 - Li Hao; Pi ChaoJie; Weiqing Chen; Zhou Min; Wei Jumeng; Yi Jianhong; Song Peng; Yakovlev A. N. Aleksey Nikolaevich; Zhong Yang; Yu Xue; Qiu Jianbei; Xu Xuhui (2021, 2021)
Title screen